Book-Burning and the Uses of Writing in Ancient Rome: Destructive Practice between Literature and Document. (10th July 2017) - Howley, Joseph A.
ABSTRACT: This article examines the burning of written material at Rome from the Republican period until the rise of Christianity, using the lens of book history. It considers why and how Romans burned written material, gathering for the first time all testimony of burning any kind of writing, and examines responses to these burnings in ancient discourse. A capacious, book-historical approach to Roman book-burning shows that differences in practice and uses — of books as opposed to documents, for example — account for the different consequences Romans saw for burning different written media.